PKM. BUDIDAYA LEBAH MADU KELE AGROWISATA ETNO BALI DI DESA BAHA, KECAMATAN MENGWI KABUPATEN BADUNG - I Komang Sukendra; I Made Darmada; I Made Subrata (LP3M Universitas PGRI Mahadewa Indonesia, 2023)
Balinese Ethno Bee Agrotourism is located in Baha village, Mengwi District, Badung Regency, Bali Province, which is engaged in cultivating honey bees, Kele is a partner in the Community Partnership Program (PKM) activities. The aim of this PKM is to overcome pests that attack Kele honey bees in an effort to increase the production of Kele Honey Bee Cultivation, and to increase sales of honey production from Kele Honey Bee Cultivation. The partner priority problems being assisted are as follows: (1) Pest problems in kele honey bee cultivation. (2) Marketing problems. The solution to deal with all attacks from bee enemies, beekeepers must look for and know the prevention: 1) to prevent ants from entering the bee house, the legs supporting the bee house are smeared with oil or put in a bowl filled with water. To prevent night moths, you can do this by keeping the bee house clean, making the door smaller so that the butterflies cannot enter, strengthening the colony and setting traps at night. If eggs, caterpillars and moths are found in the nest, they must be immediately removed and destroyed. Strengthens bee colonies so they can kill bacteria that attack larvae. Take the infected comb, then destroy it by burning it. Likewise, dealing with lizard and toke attacks requires traps. 2) For marketing, there needs to be online and off-line marketing promotions. The group continues to improve production quality, maintains the quality of honey sold to consumers, makes bottle packaging as attractive as possible and contains special labels to maintain the good name of the producer.